Uwarunkowania komunikacyjne a pododmiany recenzji muzycznej (na przykładzie recenzji twórczości grupy Depeche Mode) = Music review and its varieties with respect to the communication situation (on the basis of Depeche Mode music reviews) - Majdańska-Wachowicz, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to examine the communication situation in the music reviews with reference to the identity of the speaker and the addressee. The functions and patterns of the speaker and the addressee may have an enormous influence on the structure of the review, its content, language, and stylistics.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie